Growing teratoma syndrome of the ovary: a case report and literature review - Tao, Jiaying; Shi, Zhixian; Li, Mulan; Li, Tingting (Frontiers in Oncology, 2024)
Growing teratoma syndrome (GTS) is a rare condition that arises secondary to malignant germ cell tumors. It is characterized by an enlarging abdominal mass during or after chemotherapy, normal tumor markers, and histopathological indications of mature teratoma components. Awareness of GTS is limited, and it is often mistaken for disease progression or recurrence. This misdiagnosis can lead to delayed treatment and increased risk of complications. Therefore, early identification of GTS is crucial to avoid unnecessary systemic treatments and reduce financial burden. GTS is unresponsive to chemotherapy or radiotherapy and complete surgical resection is the sole therapeutic strategy. In this report, we present a case of GTS in a 20-year-old female following treatment for immature teratoma, alongside a review of the relevant literature aimed at enriching our insight into the clinical manifestations of GTS.